Code-mixing by a content creator Gita Savitri Devi: How and why? (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2022)
Code-mixing, which is the use of two or more languages that are mixed in one utterance, is commonly practiced by bilingual or multilingual people. Then, this study aims to find out the types and the reasons for code-mixing performed by Gita Savitri Devi, a content creator, in one of her videos on YouTube channel entitled "Plis Stop Nyebarin Hoaks!! Beropini Eps. .55". Qualitative descriptive method is used to conduct this study, and the data are analyzed using Hoffman’s theory (1991). The results of this study indicate that there are three types of code-mixing that are found in the video, namely intra sentential code-mixing, intra lexical code-mixing and involving a change of pronunciation. Furthermore, the writers also find three reasons why code-mixing is utilized, among others are: (1) talking about a particular topic; (2) being empathetic or emotional about something; and (3) repetition used for clarification. The existence of code-mixing in our daily life is able to facilitate us to language learning. However, there are still some mistakes in using the language such as dictions and ungrammatical structure. Therefore, we have to be careful in using the language and adjust it with the society to avoid miscommunication.